The effects of Phyllanthus amarus extract on the reproductive functions of male rats - Kueh, Ronnie Boon Lin (2001)
Global population has grown at such an alarming rate that it is critically straining the planet's resources. Thus regulating human fertility with an effective and inexpensive remedy, for example from plant sources is an attractive proposition. In this study, Phyllanthus amarus aqueous extract was given orally at 50, 100, 250 and 500mglkg body weight daily for 90 days to male rats to investigate its effect on the male reproductive function. Clomiphene citrate (a known male anti·fertility agent) was given orally at 5mgllOOg b. w. for comparison. The extract treatment lowered the fertility index (100, 250 and 500 mglkg b.w.) but litter size was not affected. Testicular (500mglkg b.w. group) and prostate (all extract treated groups) weights were significantly reduced. Epididymal sperm count and viability were significantly lowered (500mglkg b.w. group) without affecting motility and morphology. Testicular cholesterol showed a trend increase but was not significantly different compared to control whereas the mean volumetric proportion of testicular spermatozoa (500mglkg b.w. group) was significantly lower. Seminiferous tubules of rats given the highest dose showed interference in spermatogenesis at the spermatid level with the presence of degenerated spennatids in the lumen. In clomiphene treated rats, fertility was suppressed and the testis, epididymis, seminal vesicles and prostate were severely affected. Epididymal sperm count dropped to less than 2% of control while motility and viability were also as severely affected. Meanwhile sperm morphology revealed abnormalities of the head, neck and tail. Testicular histology showed progressive regression of the seminiferous tubules with most tubules devoid of spermatozoa and spermatid while testicular cholesterol was much higher compared to control. These results suggest that Phyllanthus amarus had a mild inhibitory effect on the male reproductive function as compared to clomiphene. These effects were reversible upon cessation of treatment. The extract possibly exerted an estrogen-like effect on the male reproductive system.